Matrix metalloproteinase 13 genotype in rs640198 polymorphism is associated with severe coronary artery disease - Vašků, Anna; Meluzín, Jaroslav; Blahák, Jan; Kincl, Vladimír; Pávková Goldbergová, Monika; Sitar, Jan; Zlámal, Filip; Bienertová-Vašků, Julie; Vítovec, Jiří (Disease markers, 2012)
Atherosclerosis as a main etiopathogenetic source for coronary artery disease (CAD) development is intimately related to dynamic changes in the extracellular matrix (ECM). Elevated levels of MMP-13 have been observed in human atherosclerotic plaques which could also involve variability in MMP-13 gene. The aim of the study was to associate rs640198 polymorphism with CAD and/or with its severity. The study comprised 1071 consecutive patients with suspected or known coronary artery disease (CAD), confirmed by coronary angiography. Genotyping for the rs640198 polymorphism in MMP-13 gene was performed using Taqman® assay. The TT and TG genotypes of rs640198 polymorphism in MMP-13 gene confer the significantly increased risk of triple vessel disease compared to patients without atherosclerotic lesions in coronary arteries (odds ratio=1.64, Pcorr=0.05). Furthermore, an increased risk of having 5 and more stenoses (odds ratio=1.90, Pcorr=0.004) was observed in TT and TG carriers (sensitivity of 0.613 and a specificity of 0.544; power of the test is 0.87). T allele of MMP-13 intron polymorphism rs640198 is associated with the severity of coronary artery disease, represented by the number of affected arteries as well as by the number of stenoses confirmed by coronarography.
Keywords: dospělí; Genetic Testing; Female; Adult; mladý dospělý; ženské pohlaví; Adolescent; lidé; Aged, 80 and over; stupeň závažnosti nemoci; matrixová metaloproteinasa 13; nemoci koronárních tepen; Male; Aged; Young Adult; polymorfismus genetický; Coronary Artery Disease; genetické testování; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Severity of Illness Index; Polymorphism, Genetic; Middle Aged; mladiství; Matrix Metalloproteinase 13; Humans